The Effectiveness of The Simulation Method and The Peer Teaching Method in Counseling on Improvement of Tooth Brushing Behavior at SD Muhammadiyah Tanjungsari Pekalongan - yodong yodong; Tuti Alawiah; Tri Anonim (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2023)
The dental health maintenance behavior of the Indonesian people in brushing their children's teeth directly is still deficient. Brushing your teeth correctly and adequately is one factor in avoiding dental and oral diseases such as caries. Therefore, it is necessary to emphasize that dental and oral health information in early childhood is needed. This study aimed to analyze the effect before and after counseling using simulation and peer teaching methods on tooth brushing behavior in SD Muhammadiyah Tanjungsari Pekalongan students. The type of research used is a quasi-experiment (quasi-experimental) with a pre-test and post-test group design. The population in this study amounted to 124 students. The sample consisted of 40 students, with 20 students being given the simulation method and 20 students being given the peer teaching method and taken by purposive sampling technique. The tests were carried out by univariate analysis and bivariate analysis, using the Mann-Whiteny test to determine differences in the effectiveness of the methods used. The statistical test results used the Mann-Withney test with results on knowledge (p=0.954), attitude (p=0.498), action (p=0.040), and index debris (p=0.001). Shows that there are differences in the effectiveness of counseling before and after using the simulation method compared to the peer teaching method; namely, knowledge is more effective using the simulation method with an average simulation of 20.60, attitudes are more effective using the peer teaching method with an average of 21.68, on the action it is more effective using the simulation method with an average of 24.30, and on the debris index it is more effective using the peer teaching method with an average of 26.55.